Working for policy - Colebatch, H. K. (Hal K.); Hoppe, Robert; Noordegraaf, Mirko (Amsterdam : Amsterdam University Press, 2010)
Though democratic government calls for well-designed and implemented policy, there is surprisingly little expert guidance available for policy makers and politicians. Working for Policy fills that gap, addressing the nature of policy work and offering necessary guidance. The contributors bring together academic and experiential knowledge in their analysis and evaluation of what modern policy makers do in given situations and of how such actions contribute to the policy process. This unique book demonstrates how scholars can help to ensure that policy makers can acquire the skills and knowledge required in governing complex modern societies.
Title from publisher's bibliographic system (viewed on 05 Feb 2021).
Keywords: Policy sciences; Decision making